Perlindungan Hukum Terhadap Foreign Direct Investment (FDI) Dalam Bentuk Kerjasama Pemerintah Dengan Badan Usaha (KPBU) - Mohamad Fadhillah Dekha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Infrastructure development in Indonesia is seen as crucial for driving economic growth, ultimately improving the well-being of the country. Foreign Direct Investment (FDI), also known as Penanaman Modal Asing (PMA), is viewed as one of the solutions to boost development in Indonesia. The Public-Private Partnership (PPP) scheme or also called Kerja Sama Pemerintah dengan Badan Usaha (KPBU) is a method of infrastructure provision and financing based on collaboration between the government and private enterprises. While the PPP is considered an effective solution, foreign investors, particularly FDI, have concerns about potential risks and losses. Therefore, there is a need for adequate legal protection to enhance investor interest in investing in Indonesia, one of which is the International Centre for Settlement of Investment Disputes (ICSID). This research aims to provide a comprehensive understanding of legal protection options for FDI investing in PPP schemes.